Green Transformational Leadership’s Impact on Employee Retention: Does Job Satisfaction and Green Support Bridge the Gap? - Ibrahim A. Elshaer; Alaa M. S. Azazz; Chokri Kooli; Abdulaziz Aljoghaiman; Osman Elsawy; Sameh Fayyad (Administrative Sciences)
This study explores the impact of green transformational leadership (GTL) on employee retention in the hospitality sector, with a specific focus on the mediating roles of employee satisfaction and perceived green organizational support (PGOS). Grounded in self-determination theory and organizational support theory, the research examines both the direct and indirect effects of GTL on employee retention. GTL fosters a sustainability-driven work environment, motivating employees through shared environmental values, which enhances their job satisfaction and perceived organizational support. These factors, in turn, strengthen employees’ commitment and willingness to stay within the organization. Using SmartPLS 3 for structural equation modeling (SEM), data collected from hospitality employees were analyzed to assess the hypothesized relationships. The findings confirm that GTL positively influences employee retention, both directly and indirectly, through the mediating effects of employee satisfaction and PGOS. This study contributes to the growing body of knowledge on sustainable leadership by highlighting the crucial role of green leadership practices in improving employee retention in environmentally conscious organizations. Implications for managers and policymakers in the hospitality sector are discussed, emphasizing the need for sustainability-driven leadership approaches to enhance workforce stability.